Job Training and Job Search Assistance Policies in Developing Countries - Eliana Carranza; David McKenzie (Institute of Labor Economics (IZA), 2023)
Governments around the developing world face pressure to intervene actively to help jobseekers find employment. Two of the most common policies used are job training, based on the idea that many of those seeking jobs lack the skills employers want, and job search assistance, based on the possibility that even if workers have the skills demanded, search and matching frictions make it difficult for workers to be hired in the jobs that need these skills. However, reviews of the first generation of evaluations of these programs found typical impacts to be small, casting doubt on the usefulness and cost-effectiveness of these programs. This paper reexamines the arguments for whether, when, and how developing country governments should undertake job training and job search assistance policies. The authors use their experience with policy implementation, and evidence from recent impact evaluations, to argue that there is still a role for governments in using these programs. However, success depends critically on program design and delivery elements that can be difficult to scale effectively, and in many cases the binding constraint may be a lack of firms with job openings, rather than a lack of workers with the skills to fill these openings.
Keywords: J22; J23; J24; J64; M53; O12; O15; 330; active labor market policies; job search assistance; job training